NEET youth in Kazakhstan, Uzbekistan, Kyrgyzstan: general and specific parameters - Khusainova, Zh.S.; Gazizova, M.R.; Zhartay, Zh.M.; Gordeyeva, Y.A.; Nurekenova, E.S. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this research is to study general and specific parameters of NEET youth in Kazakhstan, Uzbekistan, and Kyrgyzstan. Methods: Methods of system, dynamic, structural analysis. Findings: A comprehensive description of the socio-economic differentiation of youth in the labor markets of Kazakhstan, Uzbekistan, and Kyrgyzstan allowed determining the parameters of NEET-youth, including NEETunemployment. Conclusions: As a result of the study, the material was obtained, the analysis of which allowed to identify general and specific parameters of NEET-youth in Kazakhstan, Uzbekistan, Kyrgyzstan, such as reduction of NEETunemployment rates, which are typical for the countries, as well as to pay attention to the problem of migration flows of young people. In addition, the mechanism of modern youth labor markets in Kazakhstan, Uzbekistan, and Kyrgyzstan is studied. The completed work allows identifying the following prospects for further research on the topic, which are determined by the need to study the causes of NEET youth in Kazakhstan, Uzbekistan, and Kyrgyzstan.